Seroprevalence Of Infectious bursal disease virus In Local Chickens In Udu Local Government area Of Delta State, South East Nigeria (2015)
Infectious Bursal Disease Virus (IBDV) poses a great global threat to the poultry industry. Knowledge of the occurrence of the disease is important in the design and implementation of acontrol program, therefore this study determines the seroprevalence of IBDV in local chickens in Udu Local Government Area of Delta State. 250 chickens were bled by exsanguination and sera obtained were screened using Agar Gel Immunodiffusion (AGID) test. The seropositivity was 51.6%, which is indicates endemicity of the disease. Biosecurity and good sanitary measures are recommended. Molecular characterization of the strains should be carried out for inclusion in generic vaccines.